A light-scattering study of Al2O3 abrasives of various grit sizes. (September 2016) - Heinson, Yuli W.; Chakrabarti, Amitabha; Sorensen, Christopher M.
Abstract: We report light scattering phase function measurements for irregularly shaped Al2 O3 abrasive powders of various grit sizes. Q-space analysis is applied to the angular scattering to reveal a forward scattering regime, Guinier regime, power law regime with quantifiable exponents, and an enhanced backscattering regime. The exponents of the power laws for Al2 O3 abrasives decrease with increasing internal coupling parameter ρ ′, which is in agreement with previous observations for other irregular particles. Unlike other dust particles previously studied showing single power laws under Q-space analysis, the largest three abrasives, for which ρ ′ ≳ 100, showed a kink in the power law, which is possibly due to the higher degree of symmetry for the abrasives than for all the particles studied previously. Direct comparison of the 1200, 1000, and 800 grit abrasive scattering to scattering by corresponding spheres shows that the scatterings approximately coincide at the spherical particle qR ≃ ρ ′ crossover point. Furthermore, the scattering at the maximum qR = 2 kR by the irregularly shaped abrasives is close to the geometric centers of the glories of the spheres. Highlights: Scattering by irregularly shaped abrasive particles measured. Six sizes of abrasives are studied. Q-space analysis indicates power laws but a kink appears for large size. Abrasive and spherical particle scattering are compared with Q-space analysis.